Diagnostic accuracy of point-of-care tests for hepatitis C virus infection: a systematic review and meta-analysis. - Mehnaaz Sultan Khuroo; Naira Sultan Khuroo; Mohammad Sultan Khuroo (PLoS ONE, 2015)
Point-of-care tests provide a plausible diagnostic strategy for hepatitis C infection in economically impoverished areas. However, their utility depends upon the overall performance of individual tests.A literature search was conducted using the metasearch engine Mettā, a query interface for retrieving articles from five leading medical databases. Studies were included if they employed point-of-care tests to detect antibodies of hepatitis C virus and compared the results with reference tests. Two reviewers performed a quality assessment of the studies and extracted data for estimating test accuracy.Thirty studies that had evaluated 30 tests fulfilled the inclusion criteria. The overall pooled sensitivity, specificity, positive likelihood-ratio, negative likelihood-ratio and diagnostic odds ratio for all tests were 97.4% (95% CI: 95.9-98.4), 99.5% (99.2-99.7), 80.17 (55.35-116.14), 0.03 (0.02-0.04), and 3032.85 (1595.86-5763.78), respectively. This suggested a high pooled accuracy for all studies. We found substantial heterogeneity between studies, but none of the subgroups investigated could account for the heterogeneity. Genotype diversity of HCV had no or minimal influence on test performance. Of the seven tests evaluated in the meta-regression model, OraQuick had the highest test sensitivity and specificity and showed better performance than a third generation enzyme immunoassay in seroconversion panels. The next highest test sensitivities and specificities were from TriDot and SDBioline, followed by Genedia and Chembio. The Spot and Multiplo tests produced poor test sensitivities but high test specificities. Nine of the remaining 23 tests produced poor test sensitivities and specificities and/or showed poor performances in seroconversion panels, while 14 tests had high test performances with diagnostic odds ratios ranging from 590.70 to 28822.20.Performances varied widely among individual point-of-care tests for diagnosis of hepatitis C virus infection. Physicians should consider this while using specific tests in clinical practice.